Users' Perspectives About the Potential Usefulness of Online Storylines to Communicate River Research to a Multi-disciplinary Audience. Issue 7 (3rd October 2019) - Cortes Arevalo, Vivian Juliette; Verbrugge, Laura N. H.; Haan, Robert-Jan den; Baart, Fedor; van der Voort, Mascha C.; Hulscher, Suzanne J. M. H.
ABSTRACT: Effective communication practices are needed to support adaptive, collaborative and integrative environmental management. We propose the use of online storylines to communicate scientific outcomes in a way that is captivating, easily understood and accessible. Based on 20 interviews, we identified important attributes for the storyline content, structure and user interaction. We designed a storyline example about stakeholders' perceptions of a river management intervention with consequences on the landscape. The intended audience consists of multi-disciplinary researchers and practitioners that could consider or apply research solutions outside their field of expertise in river management. We introduced the example in a workshop with 14 participants from research and practice. Our findings highlight the importance of including narrative elements via images, interactive figures and timelines to illustrate the research context. Moreover, storylines should explicitly state benefits as well as the limitations of the river research and include a glossary to clarify specific terms.